2013
DOI: 10.1155/2013/965103
|View full text |Cite
|
Sign up to set email alerts
|

Depression Symptoms and Risk Factors in Adult Emergency Department Patients: A Multisite Cross-Sectional Prevalence Survey

Abstract: Objectives. To identify the proportion of adult emergency department (ED) patients who screen positive for depression. Secondary aims were to identify factors associated with a positive depression screen and determine predictors of a positive depression screen. Methods. This cross-sectional, prevalence survey of ED patients was conducted at two inner-city hospitals. 350 ED patients were screened for depression using the Patient Health Questionnaire-9 (PHQ-9). Clinical and demographic risk factors were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…One study reported data on the presence of depression in ED patients with abdominal pain (without narrowing to undifferentiated or recurrent pain) 51 . Using the PHQ‐9 tool and a cutoff score of ≥10 to define positivity, Khav et al 51 reported that five of 48 (10.4%) patients screened positive for depression. Also, patients presenting with abdominal pain were not more likely to have a positive depression screen than other complaints (10.0% vs. 14.3%, p = 0.410) 51 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported data on the presence of depression in ED patients with abdominal pain (without narrowing to undifferentiated or recurrent pain) 51 . Using the PHQ‐9 tool and a cutoff score of ≥10 to define positivity, Khav et al 51 reported that five of 48 (10.4%) patients screened positive for depression. Also, patients presenting with abdominal pain were not more likely to have a positive depression screen than other complaints (10.0% vs. 14.3%, p = 0.410) 51 …”
Section: Resultsmentioning
confidence: 99%
“…Using a cutoff of ≥5 for positivity, 42 of 83 (50.6%) were positive. One study reported data on the presence of depression in ED patients with abdominal pain (without narrowing to undifferentiated or recurrent pain) 51 . Using the PHQ‐9 tool and a cutoff score of ≥10 to define positivity, Khav et al 51 reported that five of 48 (10.4%) patients screened positive for depression.…”
Section: Resultsmentioning
confidence: 99%
“…While the prevalence of depression in the general population is believed to be 2%-3%, it can be as high as 22%-32% in patients who present to the accident and emergency department (3,4). Identifying depression is important as it can contribute to the patient's presenting condition and can have a profound effect on their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the current case, lumbosacral plexopathy was considered to have been caused owing to extensive edema and fluid present around the plexus, which was a consequence of rhabdomyolysis as a result of sustained pressure that occurred because of immobility caused by drug overdose. While the prevalence of depression in the general population is believed to be 2%-3%, it can be as high as 22%-32% in patients who present to the accident and emergency department (3,4). Identifying depression is important as it can contribute to the patient's presenting condition and can have a profound effect on their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Newly established EDs are increasing in the country and it is essential that our programs and policies be more sensitive to the patients' needs. Screening patients for MH disorders in the ED is recommended (21,22).…”
Section: Introductionmentioning
confidence: 99%